Geração, fluxo e uso da informação em ocupações de agências de turismo do Rio de Janeiro: estudo preliminar - Luengo Medina, Arturo Guillermo (1991)
Study on information transfer in travel agencies using model of communication, the technique of occupational analysis and theories of Information Science. A theoretical model with these elements is constructed and evaluated against the case studies of five travel agencies od Rio de Janeiro The conclusions are that the occupational amalysis technique is adequate for establishing the dynamics of the elements in the communication model; the theories of Information Science can contribute for the analysis of the generation, flow and use of information in the travel agencies. More research is recommended for the understanding and application of the theory os system analysis for these type os study The conclusions are that the occupational amalysis technique is adequate for establishing the dynamics of the elements in the communication model; the theories of Information Science can contribute for the analysis of the generation, flow and use of information in the travel agencies. More research is recommended for the understanding and application of the theory os system analysis for these type os study.